I love my gay son, the leatherman - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows a woman holding a sign that reads, "I love my gay son, the leatherman". The word love is represented by a heart shape. Beside her is a man, most likely her son, who is wearing a leather cap, leather vest and has what looks like a handle of a whip hanging over his shoulder.